DESCRIPTION OF GADGET ADDICTION, SLEEP QUALITY, AND STUDENTS LEARNING ACHIEVEMENT AT SD NEGERI 1 SIDODADI LAWANG IN 2019 - Wibowo, Dimas Cahyo; Fitriani, Della Wahyu; Kimresti, Ananda Febina; Ahkami, Alfan; Nastiti, Isna Sandria; Auliani, Syarifah Dwi; Ermawati, Siti; Andriani, Sabrina Rizki; Sulistiawati, Sulistiawati; Raharjo, Priyo (Journal of Community Medicine and Public Health Research, 2020)
In this globalization era, technology is increasing rapidly. One of the technologies is a gadget/device. Gadget users come from various backgrounds, ranging from adults, the elderly, and even children. The Daily Mail reports that 70% of elementary school-aged children can easily use a gadget. The use of gadgets can have both positive and negative effects on children. The negative effect of using a gadget is affecting the quality of sleep and learning achievement on children. The study aimed to describe gadget addiction, sleep quality, and learning achievement of children focused on grades 5th and 6th at SD Negeri 1 Sidodadi Lawang. A descriptive study method. The total population of grade 5th and 6th students at SD Negeri 1 Sidodadi Lawang are 96 students. Data were taken by using Smart Addiction Scale, Pittsburgh Sleep Quality Index questionnaires, and students' report cards. The distribution of gadget addiction levels in this study was 21 people (21,9%) with a low level, 72 people (75%) with a moderate level, and 3 people (3,1%) with a high level. There were 73 people (76%) with poor sleep quality and 49 people (51%) with poor learning achievement. The level of gadget addiction in 5th and 6th-grade students at SD Negeri 1 Sidodadi Lawang was dominant in the medium level, sleep quality was dominant in the poor level.